Antibiotic protected silver nanoparticles for microbicidal cotton. Issue 1 (3rd January 2019) - Montagut, Ana Maria; Granados, Albert; Ballesteros, Anna; Pleixats, Roser; Llagostera, Montserrat; Cortés, Pilar; Sebastián, Rosa María; Vallribera, Adelina
Abstract: Surface coating of metal nanoparticles is one of the major aspects to be optimized in the design of antimicrobial nanoparticles. The novelty of this work is that antimicrobial derivatives have been used as stabilizers to protect silver nanoparticles (Ag NPs). Microbicidal activity studies of fabricated cotton textiles coated with these Ag@Antibio were performed. Protective ligand layers of Ag NPs resulted to be a deterministic factor in their antimicrobial activity. The best bactericidal activity was obtained forFabric TAM (coated with Ag NPs with triarylmethane derivates in surface, Ag@TAMSH ), with a bacterial decrease of 3 log units for the S. aureus strain. Intrinsic antibiotic activity and partial positive charge of theTAMSH probably enhanced their antimicrobial effects.Fabric Eu (coated with Ag NPs with eugenol derivates in surface, Ag@EugenolSH ) andFabric FQPEG (coated with Ag NPs embedded in PEG-fluoroquinolone derivatives in surface, Ag@FQPEG ) displayed antibacterial activity for both Staphylococcus aureus and Pseudomonas aeruginosa strains. These coated antimicrobial cotton fabrics can be applied in different medical textiles. Graphical abstract: